GelMA@LNP/AST Promotes eNOS-Dependent Angiogenesis Through Autophagy Activation for the Treatment of Hind Limb Ischemia - Lai L; Wu H; Peng L; Zhang Z; Wu X; Zheng S; Su Z; Chu H (International Journal of Nanomedicine)
Lingzhi Lai,1 Hao Wu,1 Liang Peng,2 Zhen Zhang,3 Xinfan Wu,1 Shuo Zheng,3 Zekang Su,3 Hongxing Chu3 1Maoming People’s Hospital, Maoming, Guangdong, People’s Republic of China; 2The First People’s Hospital of Guiyang, Guiyang, Guizhou, People’s Republic of China; 3Stomatological Hospital, School of Stomatology, Southern Medical University, Guangzhou, Guangdong, People’s Republic of ChinaCorrespondence: Hongxing Chu, Stomatological Hospital, School of Stomatology, Southern Medical University, Guangzhou, 510280, People’s Republic of China, Tel +86-13533856675, Email chuhongxing22@smu.edu.cnPurpose: Limb ischemia is a refractory disease characterized by insufficient angiogenesis and tissue necrosis. Currently, the primary clinical treatment method is surgical intervention; however, the prognosis for patients with severe limb ischemia remains unsatisfactory. Although some studies have evaluated the effects of using bioactive factors to promote neovascularization and tissue repair, the clinical outcomes have not met expectations, possibly due to the difficulties in maintaining biological activity and avoiding potential side effects. Traditional Chinese medicine, specifically astilbin (AST), is a potential therapeutic agent in promoting tissue regeneration. However, there have been no reports on its efficacy in treating limb ischemia through promoting angiogenesis.Materials and Methods: In this study, we prepared AST-loaded lignin nanoparticles (LNP/AST) with sustained-release functionality, which were mixed with GelMA hydrogel (GelMA@LNP/AST). The angiogenic effects were evaluated in a mouse model of hind limb ischemia. To further investigate the mechanism of angiogenesis, human endothelial cell line EA.hy926 was exposed to different concentrations of AST. The effects of AST on cell migration and angiogenesis were studied using wound healing assays and angiogenesis assays. The changes in angiogenesis markers, autophagy markers, and eNOS levels were detected using qPCR and Western blotting. 3-MA was used to assess the role of autophagy in the activation of eNOS mediated by AST and its subsequent angiogenic effects.Results: GelMA@LNP/AST significantly promoted blood flow recovery in mice with hind limb ischemia. This effect was mainly attributed to the enhanced migration and angiogenic capabilities of endothelial cells mediated by AST. A potential underlying mechanism could be that the autophagy induced by AST increases eNOS activity.Conclusion: GelMA@LNP/AST enables complete revascularization in female mice after hind limb ischemia, thereby achieving limb preservation and restoring motor function. Given the good therapeutic potential of the GelMA@LNP/AST in revascularization, it may become an effective strategy for successfully salvaging limbs in cases of limb ischemia.Keywords: astilbin, endothelial cells, autophagy, eNOS, angiogenesis